BcRISP1, isolated from non-heading Chinese cabbage, decreases the seed set of transgenic Arabidopsis. (10th December 2014) - Liu, Tongkun; Qian, Yu; Duan, Weike; Ren, Jun; Hou, Xilin; Li, Ying
Abstract: Mitochondria are the energy sources of plant cells and are involved in regulating cell development. Ubiquinol–cytochrome c reductase iron-sulfur protein, which is necessary for mitochondrial respiration, is a subunit of mitochondrial electron transport chain multimeric enzyme complexes. To better understand the biological function of the ubiquinol–cytochrome c reductase iron–sulfur protein, the full-length cDNA of BcRISP1 was cloned; it was found to contain 810 base pairs and encode 269 amino acids. Unusually, high expression of the BcRISP1 gene in the archesporial cell stages was determined by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis of cytoplasmic male sterile lines and maintainer lines. The seed set was affected by the overexpression of BcRISP1, and shorter siliques with lower seed sets were observed in 35S :: BcRISP1 Arabidopsis plants. These characteristics may have resulted from the reduced formation of pollen and impaired pollen tube growth. qRT-PCR results revealed that in 35S:: BcRISP1 plants, the expression levels of the mitochondrial respiratory chain-related genes, COX10 and RIP1, were enhanced, whereas the expression levels of QCR7 and SDH2-1 were reduced. This result implies that overexpression of BcRISP1 in transgenic Arabidopsis plants may disrupt the mitochondrial electron transport chain by affecting the expression of mitochondrial respiratory chain-related genes and therefore, reducing the seed set. Pollen development: Respiratory gene crucial to fertility: Overproduction of a key protein disrupts respiration in plants, lowering pollen and seed production. Making pollen is an energy-demanding process fueled by respiration, carried out in cell components called mitochondria. Any mitochondrial defect can therefore have severe consequences for pollen production and may even result in male sterility. A team led by Ying Li at Nanjing Agricultural University have identified a gene, BcRISP1, which has dramatic effects on male fertility. BcRISP1 encodes a protein component of the electron transport chain, a key mitochondrial pathway. The team transferred BcRISP1 genes from male-sterile Chinese cabbage into the model plant Arabidopsis . They found that increased BcRISP1 activity resulted in smaller male floral parts, decreased pollen production, impaired pollen tube growth and, ultimately, fewer, smaller fruits containing fewer seeds.